Conservação, viabilidade e vigor de diásporos e crescimento inicial de mudas de aroeira (Myracrodruon urundeuva Fr. Allem.) - Caldeira, Sidney Fernando (2007)
The increase of the antropic action on the different forms of vegetation imposes the necessity to study the forest species, as much as for its conservation, as for its use in environment and productive plantations. If the species is still widely explored in function of the quality of its wood and of other types of products, they increase the risks for its extinction, and the Myracrodruon urundeuva ( aroeira ) is a species that fits in these aspects. The seed still is the most popular and common form of reproduction of the majority of the forest species, and also for its "ex-situ" conservation. However, the majority of the works on storage is conducted in cold or dry chambers, or its combination, of high cost, for periods around 12 months, and not always they reach the variation of the packages, in relation to the permeability. The option of keeping the quality of diasporas of "aroeira", deriving of seeds collection area, in Cuiabá, Brazil, and cheaper conditions to be stored, and of this form, accessible to more users was evaluated under different forms. In controlled chamber for a conditioning air device, the viability of diasporas of "aroeira" was conserved up to 30 months of storage, while the vigor was kept up to six months, independent of the type of packing used, since the impermeable one, until the total permeate one. In room environment the viability and the vigor were been reduced, at the age of six months, but in lesser speed, when the diasporas were conditioned in packing of can and polyethylene bag; at the age of 12 months the deterioration increased and at the age eighteen it was complete. Positive and significant correlations between the methods of analysis of viability as well as of vigor had been observed. The test of accelerated ageing presented resulted satisfactory to evaluate the quality of the diasporas of aroeira , while the tests of electric conductivity and of the diasporas thousand mass had not been adjusted. The evaluation of the initial development of seedlings, produced from the diasporas stored under different conditions, resulted in lesser values of height, diameter of collar and total dry substance mass, in relation to produced seedlings with the diasporas just harvested. However, with the development of the seedlings, these differences did not remain and presented inferior as well as superior values, in relation to the previous evaluations. It is possible to keep the viability of diasporas of aroeira , for at least up to 30 months, and its vigor up to six months, with its storage in controlled chamber.